Development of a hand operated diamond cut mesh drum abrasive ginger peeler - R Visvanathan, E Jayashree, (Journal of Spices and Aromatic Crops, 2013)
Peeling of fresh ginger is an important operation done before drying to enhance the drying process and is generally done manually. A mechanical ginger peeler was developed with its peeling drum made of diamond cut mesh. Peeling trials were conducted for varying drum loads (5 kg, 6 kg and 7 kg), for varying drum speeds (20 rpm, 25 rpm and 30 rpm) and for different peeling durations (5 m, 10 m and 15 m) to determine the peeling efficiency and material loss in the developed peeler. It was found that peeling of ginger was associated with the material loss. The optimum machine parameters for maximum peeling with minimum loss was obtained at a drum load of 7 kg per batch, operated at a drum speed of 30 rpm for a peeling duration of 15 min, to produce sufficiently peeled ginger. The peeling efficiency and material loss at the optimum conditions were determined as 59.43% and 4.76%, respectively. The ginger obtained after mechanical peeling was dried and the quality was determined. It was found to have essential oil of 2.0%, oleoresin of 4.6%, moisture content of 9.82% and crude fibre content of 2.5%.